The microcosm of global investigative journalism: Understanding cross-border connections beyond the ICIJ. (1st June 2019) - Gearing, Amanda; Berglez, Peter
Investigative journalism across national borders is well known for the large projects, initiated by the International Consortium of Investigative Journalists (ICIJ), with hundreds of reporters in many countries who collaborate to produce coverage such as the Panama Papers. However, there are also many examples in the field of global investigative journalism that are microcosms of their larger counterparts. These smaller or 'microcosm' cross-border collaborations are instigated and carried out by a small group of reporters, possibly including freelance reporters. Like their larger counterparts, 'microcosm investigations' can also lead to sociopolitical change and thus are deservedly classified as investigative journalism. Microcosm investigations can therefore be viewed as part of a suggested global fourth estate that is calling power to account. The purpose of the article is to examine the characteristics of 'microcosm'-oriented global investigative journalism and to demonstrate the similarities and differences compared with its larger and more visible counterpart. The empirical material consists of interviews with Australian journalists who were shortlisted as finalists and who won national journalism awards, sponsored by the Walkley Foundation. The findings indicate that new technologies that enable cross-border collaboration are enabling the emergence of a global fourth estate. In the concluding discussion it is argued that for the expansion and mainstreaming of global investigative journalism, the multiple small-scale projects undertaken should collectively be viewed as equally important, if not more important, than the fewer but larger and better-known collaborations. Microcosm collaborations offer opportunities for the proliferation of cross-border media coverage that can be accomplished even by relatively small media outlets.